Pengaruh Suhu dan Lama Pemanasan terhadap Karakteristik Ikan Tongkol Olahan yang Direndam Dalam Larutan Asap Cair Batang Bambu Tabah (Gigantochloa nigrociliata BUSE-KURZ) - Turnip, Luber; Widia, I Wayan; Kencana, Pande Ketut Diah (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 8 No 1 (2020): April, 2019)
Tuna has a high protein and water content, and has solid meat. But tuna is also very easy to damage. The cause of damage fish is a high water content which can cause microorganisms to multiply easily. Fumigation with  liquid smoke is safer and more practical than conventional fumigation, because liquid smoke contains phenol, carbonyl and organic acids which are useful for providing a distinctive taste and as preservatives in fish. The liquid smoke comes from stem of tabah bamboo ( Gigantochloa nigrociliata Buse-Kurz). The purpose of this study was to determine the effect of temperature and heating time on the characteristics of processed tuna which soaked in liquid smoke stem of tabah bamboo and to find out the temperature and heating time of the best organoleptic characteristics of processed tuna which soaked in a solution of liquid smoke stem of tabah bamboo. The method used is Factorial Completely Randomized Design with two factors. The first factor is the treatment of heating temperature which consists of three levels, and the second factor is the treatment of heating time which consists of three levels. Each treatment was repeated twice. The best combination of treatments is the heating temperature of 100?C, heating for 4 hours produce pH 5.5, water content 58.06%, ash content 1.69%, protein content 18.29%, hedonic color test 3.94, aroma test hedonic 4.28, hedonic texture test 4.72, hedonic taste test 4.5, texture scoring test 4.83, and the overall acceptance scoring test is 4.39. Keywoard : smoked tuna, liquid smoke, tabah bamboo.